LITERATURE REVIEW ETNOBOTANI: POLA PEMANFAATAN TUMBUHAN OBAT OLEH MASYARAKAT ADAT - Syalsa Nadya Zahara; Reki Kardiman (Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2026)
The use of medicinal plants by indigenous people is a form of local wisdom that is still preserved today. Indonesia's high biodiversity contributes to the development of traditional knowledge in the use of plants as natural remedies. This review article aims to analyze patterns of medicinal plant use by indigenous people, identify the most commonly used plant species, and understand how they are processed and utilized in traditional medicine. The method used was a literature review of various national and international scientific articles obtained through Google Scholar and ScienceDirect using the keywords